O uso do laser como intervenção artística: a obra circundante como análise de caso - Trombini, Maria Angelica (2022)
The discussion about laser light as an artistic language is presented as a possible calligraphy in the two-dimensional space of the canvas. Furthermore, our research on the nature of laser as an artistic medium is placed at an intersection with the Science of Mathematics, which will support this argument. This research with the laser as a pictorial language will focus on a work of my own, Surrounding, to investigate questions: how the form and the content of its nature in the plane of the canvas. At first, the research will raise the scientific path of the laser and its use as a plastic constructive element in other artistic works, starting with the exhibition ‘Art from Light’, by ZKM, held in Germany in 2003, whose theme is light as a vehicle for building an artistic construction. Therefore, we went through the pictorial expressions in the space of pictorial art, which used light as possibilities of forms, both in figurative images and in abstract images. All this contextualization of science and pictorial art aims to answer the following questions, namely: is laser a seasonal artistic medium, or not? And if so, would the laser have the power to leverage other artistic hybridizations? And if there is such a propensity, what is the potential that this element has in generating residual elements of an artistic language constructed by the bias of geometry